Achieving financial well being through the role of social capital and human capital - Arifin, Rosyid; Ratnawati, Ratnawati; Ningsih, Ayu Agus Tya (Trigin Publisher, 2025)
Research purposes: express the meaning based on the results of the analysis of the direct influence of social capital and human capital on financial well-being. Method: The analysis tool used is a structural equation model with Partial Least Square. The sample in this study was 52 members of the women's fishermen's association at the Sendang Biru Fish Auction Place in Malang Regency.Research result: explains that social capital does not directly affect financial well-being, but human capital directly has a significant effect on financial well-being. Theoretical Contribution/Originality: The novelty of this study contributes to the Resource-Based Theory (RBT) which focuses on factors that increase the financial welfare of female fisherwomen through intangible assets, namely social capital and human capital.